Neurophysiological monitoring and risk factors for white cord syndrome in cervical spondylotic myelopathy - Ahmed Hamdy Ashry; Ayman Tarek Mahmoud; Mohamed Adel Ghoneim (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Intraoperative neurophysiological monitoring (IONM) is a critical tool used during cervical spine surgeries to detect neurological deficits in real time, potentially preventing complications such as white cord syndrome (WCS). This study evaluates the effectiveness of IONM and identifies specific risk factors associated with the development of WCS. We conducted a retrospective analysis of 400 cases of cervical spondylotic myelopathy from 2017 to 2023. Patients were categorized into two groups based on whether IONM was utilized during surgery. Demographic, clinical, radiological, and surgical data were collected. The degree of myelopathy was assessed using the Modified Japanese Orthopedic Association (MJOA) scale. IONM employed both motor-evoked potentials (MEPs) and somatosensory-evoked potentials (SSEPs) for neurological function assessment. Results While IONM exhibited an 80% sensitivity in identifying WCS, its specificity was only 73%, indicating a significant rate of false positives. Additionally, several risk factors were identified, including comorbidities, such as diabetes and hypertension, symptoms duration exceeding 12 months, and the presence of hyperintense T2-weighted MRI signals. Despite the widespread use of IONM, there was no significant reduction in WCS incidence among patients monitored compared to those who were not. Conclusion This study underscores the importance of IONM in the early detection of WCS while highlighting its limitations in preventing the condition. Understanding the multifactorial risk factors for WCS can aid neurosurgeons in optimizing surgical strategies and improving patient outcomes.